Rock size-frequency distribution analysis at the Chang'E-3 landing site. (January 2016) - Di, Kaichang; Xu, Bin; Peng, Man; Yue, Zongyu; Liu, Zhaoqin; Wan, Wenhui; Li, Lichun; Zhou, Jianliang
Abstract: This paper presents a comprehensive analysis of the rock size-frequency distribution at the Chang'E-3 landing site. Using 84 Navcam stereo images acquired at 7 waypoints by the Yutu rover and an interactive stereo image processing system, a total of 582 rocks larger than 0.05 m in diameter were identified and measured. The statistical results of the size-frequency distribution show that the cumulative fractional area covered by rocks versus their diameter follows a simple exponential function and has a convex-up shape on log–log graphs with the slope increasing with diameter. The cumulative number of rocks versus diameter derived by numerically integrating the cumulative fractional area also shows a good fit with the data. A diameter–height relationship was also determined from height and diameter ratios. The observed rock statistics were also compared with those from other lunar missions, including the Surveyor, Apollo, and Lunokhod missions; results suggest that the rock distribution at the Chang'E-3 landing site is similar to that found by Surveyor III. Highlights: Chang׳E-3 landing site rock size frequency distribution was analyzed. Interactive stereo image processing measured 582 rocks over 0.05 m in diameter. Cumulative fractional area covered by rocks versus diameter is a simple exponential. Statistics were compared with the Surveyor, Apollo, and Lunokhod lunar missions. The Chang׳E-3 landing site rock distribution resembles that found by Surveyor III.